Automated solid-phase concatenation of Aib residues to form long, water-soluble, helical peptides. Issue 80 (9th September 2020) - Zieleniewski, Francis; Woolfson, Derek N.; Clayden, Jonathan
Abstract : Modified conditions for solid phase peptide synthesis allows repeated coupling of hindered residues, giving water-soluble peptides with up to 17 consecutive Aib residues. Abstract : Iterative coupling of 2-aminoisobutyric acid (Aib) has been achieved rapidly and efficiently using automated solid-phase peptide synthesis, employing diisopropylcarbodiimide (DIC) in the presence of ethyl cyanohydroxyiminoacetate (Oxyma). This method has allowed the first total synthesis of the fungal antibiotic Cephaibol D, and enabled the synthesis of water-soluble oligomers of Aib containing up to an unprecedented sequence of 17 consecutive Aib residues. Conformational analysis of the Aib oligomers in aqueous solution shows a length dependence in their CD spectra, with oligomers of more than 14 Aib residues apparently adopting structured helical conformations.